Comparative Studies of Renin-Null Zebrafish and Mice Provide New Functional Insights. Issue 3 (10th January 2022) - Hoffmann, Scott; Mullins, Linda; Rider, Sebastien; Brown, Cara; Buckley, Charlotte B.; Assmus, Adrienne; Li, Ziwen; Sierra Beltran, Mariana; Henderson, Neil; del Pozo, Jorge; De Goes Martini, Alexandre; Sequeira-Lopez, Maria Luisa S.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The renin-angiotensin system is highly conserved across vertebrates, including zebrafish, which possess orthologous genes coding for renin-angiotensin system proteins, and specialized mural cells of the kidney arterioles, capable of synthesising and secreting renin. Methods: We generated zebrafish with CRISPR-Cas9-targeted knockout of renin ( ren −/− ) to investigate renin function in a low blood pressure environment. We used single-cell (10×) RNA sequencing analysis to compare the transcriptome profiles of renin lineage cells from mesonephric kidneys of ren −/− with ren +/+ zebrafish and with the metanephric kidneys of Ren1 c −/− and Ren1 c +/+ mice. Results: The ren −/− larvae exhibited delays in larval growth, glomerular fusion and appearance of a swim bladder, but were viable and withstood low salinity during early larval stages. Optogenetic ablation of renin-expressing cells, located at the anterior mesenteric artery of 3-day-old larvae, caused a loss of tone, due to diminished contractility. The ren −/− mesonephric kidney exhibited vacuolated cells in the proximal tubule, which were also observed in Ren1 c −/− mouse kidney. Fluorescent reporters for renin and smooth muscle actin ( Tg(ren:LifeAct-RFP; acta2:EGFP )), revealed a dramatic recruitment of renin lineage cells along the renal vasculature of adult ren −/− fish, suggesting a continued requirement for renin, in the absence of detectable angiotensin metabolites, as seen in the Ren1 YFP Ren1 c −/− mouse. Both phenotypes were rescued by alleles lacking the potential for glycosylation at exon 2, suggesting that glycosylation is not essential for normal physiological function. Conclusions: Phenotypic similarities and transcriptional variations between mouse and zebrafish renin knockouts suggests evolution of renin cell function with terrestrial survival.